Characterization and Optical Properties of MnO Doped CuO-Containing Phosphate Glass as Absorption Filters - Abd El-Ghany, Hytham Ahmed (JOURNAL OF ADVANCES IN PHYSICS, 2018)
In order to demonstrate the intrinsic and extrinsic changes induced by MnO in the phosphate glass network, a glass system of composition 44P2O5-38ZnO-2CuO-(16-x)Na2O-xMnO (where, x = 1, 2, 3, 4, and 5 mol%) was prepared using the conventional melt quenching technique. XRD patterns confirmed the non-crystalline nature of the prepared samples. The density and molar volume as a function of MnO content were determined to characterize structure of the obtained glasses. The optical spectroscopic studies of the prepared samples were carried out over (190-1000 nm) spectral range. The prepared samples were found to behave as bandpass filters in the visible region of spectrum. The UV cutoff wavelength was shifted from 308 nm to 352 nm by increasing content of MnO which is very useful in the optical technology requirements such as ultraviolet preventing applications and the protection from UV-LASER. The optical band gap was decreased by increasing content of MnO whilst, the Urbach energy was increased. The decrease in optical band gap was attributed to the progressive increase in non-bridging oxygens (NBOs) concentration with the addition of MnO. The refractive index was found to be enhanced with the addition of MnO by the effect of increase in overall polarizability. However, the optical polarizability was found to be correlated to the chemical composition of the glass. The results reveal the role of MnO as a network modifier in the phosphate glass matrix.